The correlation between colonization and the biological properties of Lactobacillus sp. (August 2020) - Zhao, Guozhong; Cui, Man; Wang, Mengying; Chen, Wen; Li, Jingjing; Yao, Yunping
Abstract: Lactobacillus strains are used for their probiotic effects and fermentation properties. The colonization of 16 Lactobacillus strains was determined based on animal experimentation and Real-Time Quantitative PCR. Strains expressed varied amounts of colonization in the mouse gut environment, the best was shown by L. plantarum CCFM737 and L. casei CCFM736, followed by other L. plantarum and L. casei strains. L. plantarum CCFM737 and L. casei CCFM736 both colonized at a significant level for at least 2 wk. L. plantarum and L. casei showed the best biological properties, including gastrointestinal tolerance, antimicrobial activity, use of oligosaccharides, tolerance of gastrointestinal juices and adhesive properties, especially the antimicrobial properties. A significant correlation between colonization of L. plantarum and L. casei and biological properties was observed.